Analysis of Factors Affecting Consumer Behavior and Marketing Performance in the Livestock Industry - Hadiansyah Ma'sum; Heny Hendriyati; Ina Septiana; Gery Geraldy Embatau; Nuraisyah Nuraisyah (Indonesian Journal of Business and Entrepreneurship Research, 2024)
This study investigates consumer behavior and marketing performance in the chicken egg industry, with a particular focus on Li'an Meto Farm in Takalar Regency. Data were gathered through in-depth interviews with the farm's owner and customers, providing insights into the factors influencing consumer decisions. The findings reveal that consumer behavior in the region is primarily shaped by price, quality, and availability. Consumers tend to prefer chicken eggs that are affordable, of high quality, and easily accessible. Moreover, trust in the brand and the farm's reputation significantly impact purchasing decisions. Li'an Meto Farm exhibits strong marketing performance, which can be attributed to its strategic emphasis on building and maintaining good relationships with customers, alongside a commitment to consistently delivering high-quality products. These factors contribute to the farm's ability to attract and retain a loyal customer base, thereby enhancing its overall market position.